Choosing and Using Learning Media during Remote Teaching: Teachers’ Thought - Ria Lusiyani; Widya Dara Anindya (Yayasan Visi Intan Permata, 2021)
Covid-19 outbreak enforced teachers and students to adapt to the situation by doing online learning which automatically involves some online learning applications and platforms. These programs allow teachers and students to conduct the teaching and learning activities even though they are currently in different places. Therefore, choosing and using appropriate and relevant learning applications and platforms could support the online teaching and learning process to take place. This research attempts to investigate platforms and applications used by EFL teachers in Surabaya during the remote teaching. Also, factors interfering the use particular applications and platforms were studied to see teachers’ considerations in preparing online teaching platforms and applications. There are 31 EFL teachers in Surabaya who teach senior high school students participating in this research. A questionnaire and a follow-up interview were employed to obtain research data. The result revealed that there are four categories of online learning applications found in this research, including Learning Management System, Content maker, Video Conference as well as chat and messages applications. Meanwhile, four factors interfering teachers to choose and use the platform and applications were revealed: application features, school’s policy, teachers’ familiarity, and financial consideration.